2010
DOI: 10.1007/s12206-010-0208-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance analysis of heat exchanger for closed wet cooling tower using heat and mass transfer analogy

Abstract: In closed wet cooling towers, the heat transfer between the air and external tube surfaces can be composed of the sensible heat transfer and the latent heat transfer. The heat transfer coefficient can be obtained from the equation for external heat transfer of tube banks. According to experimental data, the mass transfer coefficient was affected by the air velocity and spray water flow rate. This study provides the correlation equation for mass transfer coefficient based on the analogy of the heat and mass tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…A decrease of ambient wet-bulb temperature is beneficial to improve the cooling capacity of a CWCT because the temperature difference between the air and the cooling water is increasing. This indicates that the cooling water outlet temperature has a strong positive correlation with the ambient wet-bulb temperature, which is consistent with the findings of Zheng [4], Yoo [22], and Sarker [32]. The cooling tower effectiveness was not considerably affected by the ambient wet-bulb temperature in this study, which was consistent with the results reported by Facão [11].…”
Section: Effect Of Air Flow Ratesupporting
confidence: 92%
See 4 more Smart Citations
“…A decrease of ambient wet-bulb temperature is beneficial to improve the cooling capacity of a CWCT because the temperature difference between the air and the cooling water is increasing. This indicates that the cooling water outlet temperature has a strong positive correlation with the ambient wet-bulb temperature, which is consistent with the findings of Zheng [4], Yoo [22], and Sarker [32]. The cooling tower effectiveness was not considerably affected by the ambient wet-bulb temperature in this study, which was consistent with the results reported by Facão [11].…”
Section: Effect Of Air Flow Ratesupporting
confidence: 92%
“…This phenomenon is probably the consequence of joint contributions of the spray water, the spray, and the splash. When the external surface of the heat exchanger is fully wetted by the spray water, an increase of spray water flow rate does not significantly improve the thermal performance, which is consistent with the results reported by Facão [11], Zheng [21], and Yoo [22]. The spray water temperature is a dependent variable, which is mainly determined by the status of air and process water [34,35].…”
Section: Effects Of Spray Water Flow Rate and Inlet Water Temperaturesupporting
confidence: 88%
See 3 more Smart Citations